STUDY OF CELLULAR NETWORK ARCHITECTURE IN UKRAINE AND OPPORTUNITIES OF TRANSITION TO LTE - Одарченко, Р. С.; Дика, Н. В. (Science-based technologies, 2016)
In this work, the main architectural concepts to cellular networks were analyzed, in particular, different cellular transmission networks, their architecture and technical characteristics were considered. The comparative analysis of the LTE, GSM, WCDMA networks is carried out and their common features and distinctions are selected. Also comparing of the requirements of IMT-Advanced, LTE Rel.8 and LTE-Advanced was carried out and their main shortcomings are defined. Questions of transition of the existing standards of cellular networks to the LTE network are taken up. Investigated differences in the stages of planning standards for cellular networks GSM/WCDMA/LTE, which managed to formulate the task of building a network of LTE. Also necessary input data for the primary planning of a cellular network of LTE were contoured.